Padrão de ocorrência e distribuição espacial da Chikungunya no Ceará, de 2014 a 2018 - Simião, Adriana Rocha (2019)
INTRODUCTION: Chikungunya is an infectious disease caused by a Togaviridae alphavirus transmitted mainly by Aedes mosquitoes. Between 50% and 97% of chikungunya virus-infected individuals develop signs / symptoms of fever and polyarthralgia. In Brazil the first indigenous cases occurred in 2014. In 2015 there were a higher number of notifications. However, there was a significant increase in reported cases in subsequent years, with epidemics recorded in 2016 and 2017. OBJECTIVE: To describe the introduction of the virus, the pattern of occurrence and spatial distribution of chikungunya cases and deaths in the state of Ceará. , from 2014 to 2018. METHODS: This is a descriptive study of chikungunya cases in the state of Ceará. The main source of the secondary data was the Notification Disease Information System (SINAN). Data were analyzed using Tabwin41® and Excel software. RESULTS: The first imported cases in Ceará were identified in 2014 and in 2015 there were records of the first indigenous cases. From 2016 to 2018, 201,201 suspected cases were reported. Of these, 69.3% were confirmed. The profile of those affected by chikungunya in Ceará was predominantly women (62.5%), aged 20 to 59 years (66.2%), urban residents (89.4%), with incomplete primary education (35 , 3%). The most frequent clinical signs / symptoms were fever (89.2%), arthralgia (74.4%), headache (73.6%) and myalgia (65.5%). Of those who reported pre-existing illnesses, 58.8% reported hypertension and 24.7% diabetes. In 2015, the disease was registered in five municipalities of the state, in 2016 the cases were distributed in 78.3% (144/184) of the municipalities and in 2017, 90.2% (166/184) of the municipalities registered the disease. Deaths were predominant in the acute phase of the disease (49.4%), in the age group above 70 years (60.8%) and with incomplete elementary school (49.2%). CONCLUSION: During the study period, there was a constant record of cases, characterizing the probable endemicity of the disease. The most affected population was women of working age, living in urban areas and with low education. In addition to fever and arthralgia, which make up the case definition, headache and myalgia were the most prevalent signs / symptoms. High blood pressure and diabetes were the most common pre-existing diseases. There were no clusters of municipalities with high incidences. Deaths occurred predominantly in the acute phase of the disease in the elderly with low education. These results contribute to our knowledge of chikungunya and may help mitigate future outbreaks.